Does the Occasion Justify the Denunciation?: a Multilevel Approach for Brazilian Accountants - Bernardo de Abreu Guelber Fajardo; Ricardo Lopes Cardoso (BBR: Brazilian Business Review)
Frauds represent large losses to the global economy, and one of the main means for their containment is by means of denunciations within organizations: whistle blowing. This research aims to analyze whistle blowing within the Brazilian context, considering the influence of costs and intrinsic benefits as well as aspects of the individual's interaction with his/her organization, profession and society at large. By means of a questionnaire answered by 124 accountants, a multilevel model was applied to analyze these aspects. The results demonstrate the importance of situational aspects as a positive influence in favor of denunciations. These results are useful for organizations and regulatory institutions in developing institutional mechanisms to encourage denunciation. Moreover, the results are also useful for teachers of professional ethics and members of the Federal and Regional Accounting Councils, which are dedicated to the assessment of alleged deviations from the professional code of ethics.